2016
DOI: 10.4172/jbb.1000321
|View full text |Cite
|
Sign up to set email alerts
|

A Systemic Review on Surgical Site Infections: Classification, Risk Factors, Treatment Complexities, Economical and Clinical Scenarios

Abstract: Objective: To signify the risk factors, treatment complexities, economical and clinical scenarios related to Surgical Site infection (SSIs). The second most common health care associated infection is the Surgical Site infection, which may increase morbidity and mortality rate among surgical patient and produce a greater influence on length of stay during hospitalization, readmission and economic cost.Method: A methodical literature investigation was conducted to recognize the extent of studies in relation to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The most common organisms responsible for SSI are Staphylococcus aureus (MRSA and MSSA), E. coli, coagulase-negative Staphylococci (CONS), Pseudomonas, etc. [77]. The INICC data from developing countries shows a significantly higher incidence of SSI, as compared to the data from developed countries.…”
Section: Surgical Site Infectionmentioning
confidence: 85%
“…The most common organisms responsible for SSI are Staphylococcus aureus (MRSA and MSSA), E. coli, coagulase-negative Staphylococci (CONS), Pseudomonas, etc. [77]. The INICC data from developing countries shows a significantly higher incidence of SSI, as compared to the data from developed countries.…”
Section: Surgical Site Infectionmentioning
confidence: 85%
“…Surgical Site has a statistically significant relationship with wound class at the time of surgery According to microbiological research on surgical site infection conducted at Black Lion Hospital and Hawassa Referral Hospital, Pseudomonas aeruginosa was the third most common isolate after Staphylococcus auras and coagulase-negative Staphylococci. The lowest resistance rate achieved was 25% for ampicillin, and the maximum resistance rate obtained was 100% for chloramphenicol [12,16]. Surgical site wound infection was documented in another prospective study in TikurAnbessa Hospital in 2015.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Several factors have been found as increasing vulnerability to any wound infection, with some of these factors strongly predisposed to infection. Susceptibility is increased by pre-existing disease, the length of the surgery, the wound class, and wound infection [12]. Other risk factors for wound infections include extremes of age, malignancy, metabolic illnesses, malnutrition, immune suppression, cigarette smoking, remote site infection, emergency procedures, and a long period of preoperative hospitalization [13,14] Various studies in Ethiopia have found that the prevalence of post-surgical wound infection ranges from 14.8 percent to 60%.…”
Section: Introductions Background Of the Studymentioning
confidence: 99%